2011
DOI: 10.1029/2010jc006522
|View full text |Cite
|
Sign up to set email alerts
|

Wind speed retrieval from RADARSAT-2 quad-polarization images using a new polarization ratio model

Abstract: [1] This paper presents a first attempt to analyze C-band RADARSAT-2 measurements of the normalized radar cross sections (NRCS) in quad-polarization acquisition mode (HH, VV, HV, and VH) over the ocean. NRCS in copolarizations and cross-polarizations are found to be different; the latter is independent of radar incidence angles and wind directions, but is quite linear with respect to wind speeds. We also investigate the properties of the polarization ratio, denoted PR, and show that it is dependent on incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 36 publications
5
116
4
Order By: Relevance
“…Figure 15b shows the GF-3 PR dependence on wind speed. Overall, GF-3 PR is significantly lower than the model in Zhang et al [11] for all wind speeds. There is a difference of approximately 1.0 dB between the two when the wind speed is 6 m·s −1 .…”
Section: Wind Sensitivity For the Polarization Combinationcontrasting
confidence: 56%
See 3 more Smart Citations
“…Figure 15b shows the GF-3 PR dependence on wind speed. Overall, GF-3 PR is significantly lower than the model in Zhang et al [11] for all wind speeds. There is a difference of approximately 1.0 dB between the two when the wind speed is 6 m·s −1 .…”
Section: Wind Sensitivity For the Polarization Combinationcontrasting
confidence: 56%
“…There is a difference of approximately 1.0 dB between the two when the wind speed is 6 m·s −1 . The model in Zhang et al [11] decreases with wind speed, whereas GF-3 PR remains basically unchanged. Figure 15c shows the GF-3 PR dependence on azimuth angle.…”
Section: Wind Sensitivity For the Polarization Combinationmentioning
confidence: 91%
See 2 more Smart Citations
“…Mouche et al [39] showed that the PR model of Elfouhaily [3] produced generally the best agreement with their observations and developed two new PR model using airborne real aperture radar data acquired at the C-band with both vertical and horizontal polarizations for moderate incidence angles. The first attempt to analyze C-band RADARSAT-2 measurements of the normalized radar cross-sections in quad-polarization acquisition mode over the ocean has been presented in Zhang et al [42]. Results showed that the constructed PR model with both wind speed and incidence angle dependence (SAD), in conjunction with CMOD5.N, achieved the smallest bias and standard deviation by comparing retrieved wind speeds from different CMOD algorithms with buoy measurements.…”
Section: Wind Speed Retrievalmentioning
confidence: 99%